Hubungan Penguasaan Kosakata dengan Kemampuan Menulis Teks Eksposisi Siswa SMK Negeri 3 Jember - Yessy Putri Wulandari; Fitri Sakinah; Callista Azalia Nur Firdaus; Muhammad Ibnu Hasan; Agus Milu Susetyo (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Writing proficiency is a complex language skill that involves cognitive processes and the integration of various supporting factors. This study aims to analyze the diverse elements influencing students' writing skills, encompassing both internal and external aspects, through a comprehensive literature review. The analysis reveals that internal factors, such as reading interest, have a significant positive correlation with narrative writing skills, where the breadth of insight gained from reading enriches students' cognitive structures for storytelling. Regarding instructional methods, the implementation of innovative models—such as Problem-Based Learning (PBL) and Blended Learning strategies—has proven effective in improving expository writing skills within the context of the Merdeka Belajar (Freedom to Learn) curriculum. Furthermore, the use of specifically developed teaching materials and the integration of character values in the learning process contribute positively to the quality of student compositions. Technically, the cognitive process in narrative writing is also influenced by the effectiveness of the instructional media utilized in the classroom. In conclusion, enhancing students' writing skills requires a holistic approach that combines the strengthening of reading interest, the selection of interactive learning models, and the utilization of relevant media and information technology.